Optimisasi SCADA di MPS dengan FINS UDP vs Modbus TCP via Node-RED - Subekti, Ruminto; Hadiani, Dini; Ardaneshwara, Akhtar (AI Society & STMIK Indonesia, 2024)
The increasing human population and rapid urbanization have led to a surge in the demand for manufactured products. This requires more complex and digitally connected control systems. Industrial automation, especially the use of a Programmable Logic Controller (PLC), is key to improve efficiency and productivity. However, the integration of different brands of PLCs in one system faces challenges due to differences in systems, controls, and communication protocols. Supervisory Control and Data Acquisition (SCADA) is implemented to overcome this problem by connecting the controlling device to the supervisory software. This research aims to develop Node-RED based SCADA to monitor and control Modular Production Systems (MPS) with multi brand PLC integration. Multibrand integration is applied to implement and test the performance of FINS UDP and Modbus TCP protocols. The test results show FINS UDP has a lower delay (66.85 ms) and higher throughput (3706.2 bps) than Modbus TCP, which has a delay of (348.05 ms) and a throughput of (3353.25 bps).